Technological field: technological innovation in the UK marine energy technology sector - Kampouris, Marios (The University of Edinburgh, 2016)
The aim of this thesis is to develop an innovative theoretical understanding of technological innovation as a social phenomenon and to demonstrate the results of its application to the sector of UK's marine energy technology. Via a creative analysis and critique of various theoretical approaches to technology, I identify several key elements of a theory capable of understanding technological change, which I then develop based on the critical juxtaposition of the approaches of Pierre Bourdieu and Cornelius Castoriadis. Technological innovation is understood as the ultimate outcome of the relations of cooperation and competition formed by radically creative agents, capable of ex-nihilo creation, who participate in private and public institutions of a quasi-regulated technological field. After arguing in favour of applying a primarily subjectivist epistemology with objectivist elements, I present a research methodology based on semi-structured interviews. The results of the data analysis highlight several key features of technological change as it takes place within the technological field of UK's marine energy technology. Firstly, I present the ways the technological field influences the agents therein and helps them develop their craft. Secondly, I explore how the agents of the field use their craft as they create ex-nihilo. Thirdly I show the interactions between the technological field and other social institutions/spaces such as the economic sector and the general public. Subsequently, I analyse the internal organization of the technological field and its impact upon the trajectories that technological innovation follows therein. Finally, I make the first tentative steps towards developing policy advice for the sector. I conclude that, as long as policy makers manage to develop a precise understanding of the technological field of marine energy technology, then they actually can design policy capable of positioning the technological innovations therein within a preferred path.
Keywords: technology; marine; innovation; energy; imagination